Prevalence of Obesity and Associated Risk Factors Due to Physical Inactivity Among Medical Students in Faisalabad - Liaquat, Kiran; Tariq, Ammara; Ghaffar, Tamjeed; Javed, Hina; Khan, Moha Akram; Manzoor, Urooj (International Health Review, 2024)
Obesity is defined as having a body mass index (BMI) that is higher than what is considered normal and healthy for a certain height. While excess body fat is typically the cause of obesity, factors such as fluids, excess muscle, or bone density may also contribute to obesity. The main purpose of this study was to determine the prevalence of obesity and some associated risk factors among the medical students at universities of Faisalabad due to their inactive life style. In this analytical cross sectional study, a convenience sampling technique was used to collect data from 290 medical students. The criteria included students aged between 19-23 years, while those with medically diagnosed psychological issues and trauma were excluded. Data was collected using a self-administered questionnaire, which was distributed to all the obese medical students who were conveniently accessible and could comprehend the material. The data was evaluated using the Statistical Package for the Social Sciences (SPSS) software, version 17. The results showed that 33.0% of the students were of normal weight, 23.0% were overweight, 40.5% were obese and 3.4% were severely obese. A significant association was found between obesity of the respondents and their perception about the risk factors.